Noun and Verb Production in Maternal and Child Language: Continuity, Stability, and Prediction Across the Second Year of Life. Issue 2 (2nd April 2016) - Longobardi, Emiddia; Spataro, Pietro; L. Putnick, Diane; Bornstein, Marc H.
ABSTRACT: The present study examined continuity/discontinuity and stability/instability of noun and verb production measures in 30 child-mother dyads observed at 16 and 20 months, and predictive relations with the acquisition of nouns and verbs at 24 months. Children exhibited significant discontinuity and robust stability in the frequency of nouns and verbs between 16 and 20 months (over and above the contribution of maternal measures). By contrast, mothers showed small, but significant, increases in the total number of nouns and the percentages of nouns located in the initial and final utterance positions, together with a decrease in the percentage of verbs located in the initial position. After removing the variance explained by child language, mothers' speech was stable only in the percentages of nouns located in the initial and final utterance positions. Finally, children's production of nouns at 24 months was predicted by the percentages of nouns located in the initial and final positions of maternal utterances at 16 months. Maternal measures at 20 months did not predict children's production of nouns nor for verbs at 24 months. Implications for language acquisition are discussed.